(untitled) (Revista Brasileira Multidisciplinar, 2025)
Introduction: The Covid-19 pandemic, a highly transmissible disease that has surpassed the milestone of millions of deaths worldwide and has been demanding major challenges for health systems. Many patients require an intensive care unit, which can make them more vulnerable to the risk of infection. In this context, urinary tract infection is one of the most frequent causes of infectious pathology found in medical practice. This study aims to identify the microbiological profile of patients with urinary tract infections admitted to the Covid ICU of a reference hospital. Method: descriptive exploratory study, with a quantitative approach. Carried out through documentary analysis of the results of 23 urine cultures from April to December 2020, in a reference hospital in Pernambuco. Results: Urinary tract infections (UTI) predominated in females (56.52%), with the most affected age group being 66 to 80 years, in both sexes (57%). The most present microorganisms were Klebsiella pneumoniae (26%), followed by Enterococcus faecium (22%), followed by Escherichia coli and Pseudomonas aeruginosa with the same percentage (13%). There was greater resistance to pyrazinamide, amphotericin B and habekacin, and greater sensitivity to amikacin, followed by co-trimoxazole. Conclusion: This study identified the epidemiological profile of patients with urinary tract infections admitted to the covid-19 ICU, highlighting the importance of the study to assist healthcare professionals in observing and identifying possible risks in the genitourinary system and renal function of patients. patients affected by covid-19.